The production of nitric oxide in the coeliac ganglion modulates the effect of cholinergic neurotransmission on the rat ovary during the preovulatory period - Delsouc, María Belén (2018)
The aim of the present work was to investigate whether the nitric oxide produced by the nitric oxide/nitric oxide synthase (NO/NOS) system present in the coeliac ganglion modulates the effects of cholinergic innervation on oxidative status, steroidogenesis and apoptotic mechanisms that take place in the rat ovary during the first proestrous. An ex vivo Coeliac Ganglion- Superior Ovarian Nerve- Ovary (CG-SON-O) system was used. Cholinergic stimulation of the CG was achieved by 10 −6 M Acetylcholine (Ach). Furthermore, 400 μM Aminoguanidine (AG) – an inhibitor of inducible-NOS was added in the CG compartment in absence and presence of Ach. It was found that Ach in the CG compartment promotes apoptosis in ovarian tissue, probably due to the oxidative stress generated. AG in the CG compartment decreases the release of NO and progesterone, and increases the release of estradiol from the ovary. The CG co-treatment with Ach and AG counteracts the effects of the ganglionic cholinergic agonist on ovarian oxidative stress, increases hormone production and decreases Fas mRNA expression. These results suggest that NO is an endogenous modulator of cholinergic neurotransmission in CG, with implication in ovarian steroidogenesis and the apoptotic mechanisms that take place in the ovary during the preovulatory period in rats.